Ethnomathematics Study of Islands Indigenous Peoples in Maluku Province, Indonesia - Theresia Laurens; Darma Ngilawayan; Johan Pattiasina (FKIP Universitas Lampung, 2019)
Ethnomathematics study of islands indigenous peoples in Maluku Province, Indonesia. Objectives: The aim of this study was implementation of a mathematics study in learning related to island communities’ context in Maluku. Methods: This study used methods of exploration, documentation and literature study. Findings: Many local communities in the Maluku did not realize that all selling activities, handicraft, or woven are included in mathematics in the form of fractions or geometry. Conclusion: This study concluded that the activities of selling, weaving and crafting in the community display fraction and geometry patterns Keywords:Ethnomatematics, island indigenous peoples, fractions, geometry. DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201914